A carbon dioxide-based two-component polyurethane thermally conductive adhesive and a preparation method thereof
By using the coupling reaction bridge between modified carbon dioxide-based polycarbonate diol and thermal filler in polyurethane adhesive, the problem of difficult to take into account both thermal conductivity and bonding strength in the prior art is solved, and a two-component polyurethane thermally conductive adhesive with high thermal conductivity and excellent bonding strength is achieved, which is suitable for the bonding and heat dissipation needs of the surface of the power battery PACK module.
Patent Information
- Application Number
- CN202310200837.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-03-06
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2043-03-06
AI Technical Summary
The prior art is difficult to improve the thermal conductivity of the adhesive without reducing the bonding strength, especially when the surface bonding of the power battery PACK module, the demand for the bonding and thermal conductivity of various materials is difficult to meet.
Modified carbon dioxide-based polycarbonate diol is used as the key raw material for component A. The thermal conductivity of polyurethane adhesive is improved by coupling reaction with thermal filler, while maintaining or improving the bonding strength.
It realizes the high thermal conductivity and excellent bonding strength of two-component polyurethane thermal bonding adhesive, which is suitable for the bonding and heat dissipation needs of the power battery PACK module surface, and is also environmentally friendly and green and environmentally friendly.
Smart Images

Figure BDA0004109001310000021 
Figure BDA0004109001310000022 
Figure BDA0004109001310000141
Abstract
Description
Technical Field
[0001] The invention belongs to the field of polyurethane adhesives, and in particular relates to a carbon dioxide-based two-component polyurethane thermally conductive adhesive and a preparation method thereof. Background Art
[0002] The rapid development of the new energy vehicle industry has put forward new requirements for adhesives used in power battery PACK. The surface materials of power battery PACK modules include various functional materials such as PET blue film and aluminum alloy. The structural adhesive is required to have good adhesion to various materials without surface treatment. At the same time, it is required to have a medium elastic modulus and excellent flame retardancy to meet the working conditions of high-frequency vibration of power batteries and adapt to the use of automobiles in extremely cold and high-temperature areas. In addition, as the energy density of power batteries increases, the heat released by batteries during charging and discharging per unit time increases, and the requirements for the thermal conductivity of adhesives are also increasing.
[0003] As we all know, as the amount of thermal conductive filler increases and the amount of resin decreases, the bonding strength of the adhesive gradually decreases. Although epoxy adhesives and acrylate adhesives in the prior art have extremely high bonding strength, they generally have the problem of low thermal conductivity. Although silicone thermal conductive adhesives can achieve a higher modulus of thermal conductivity, their bonding strength is very low and it is difficult to meet the needs of structural bonding.
[0004] Two-component polyurethane adhesives have advantages such as long storage cycle and adjustable modulus, and are gradually gaining attention in the structural bonding of lithium battery PACKs. However, the key raw materials in traditional polyurethane adhesives, polyol polymers, mostly come from limited fossil fuel resources, which to a large extent limits the green and environmentally friendly development of polyurethane adhesives. On the other hand, the bonding strength of polyurethane adhesives prepared using conventional polyester polyols and polyether polyols needs to be further improved, especially when the content of thermal conductive fillers is high, the bonding strength decreases more significantly.
[0005] In summary, in order to meet the growing composite needs of new energy vehicles in terms of structural bonding and heat dissipation of lithium battery PACK, how to prepare a green and environmentally friendly two-component polyurethane adhesive with excellent bonding strength and thermal conductivity has become an urgent problem to be solved. Summary of the invention
[0006] The first object of the present invention is to provide a carbon dioxide-based two-component polyurethane thermally conductive adhesive having good bonding strength and thermal conductivity.
[0007] The second object of the present invention is to provide a method for preparing the above-mentioned carbon dioxide-based two-component polyurethane thermally conductive adhesive.
[0008] The carbon dioxide-based two-component polyurethane thermally conductive adhesive provided by the present invention comprises component A and component B in a volume ratio of (1-2):1; the component A comprises an isocyanate diblocked polyurethane prepolymer, a first thermally conductive filler and an optional first auxiliary agent, and the isocyanate diblocked polyurethane prepolymer is obtained by subjecting a modified carbon dioxide-based polycarbonate diol, a castor oil polyol and a polyisocyanate to a nucleophilic addition reaction in the presence of a first catalyst; the component B comprises a polyether polyol, a polybutadiene polyol, a small molecule polyol, a second thermally conductive filler and an optional second catalyst and a second auxiliary agent; the modified carbon dioxide-based polycarbonate diol simultaneously comprises a structural unit represented by formula (I), a structural unit represented by formula (II) and a structural unit represented by formula (III):
[0009]
[0010] In formula (III), R1, R2 and R3 are each independently a C1-C5 alkyl group.
[0011] In one specific embodiment, the modified carbon dioxide-based polycarbonate diol is represented by formula (IV):
[0012]
[0013] In formula (IV), m and n represent the molar proportion of the corresponding structural units, wherein 0.90≤n≤0.97 (such as 0.90, 0.91, 0.92, 0.93, 0.94, 0.95, 0.96, 0.97 or any value therebetween), and m+n=1. It should be noted that in formula (IV), the content of the structural unit derived from propylene oxide is represented by n and the content of the structural unit derived from 1,2-epoxy-4-vinylcyclohexane is represented by m in order to reflect the molar proportion of different structural units. Formula (IV) is only used to represent the type and proportion of each structural unit, and cannot reflect the type of copolymerization reaction and the connection relationship between each structural unit. The modified carbon dioxide-based polycarbonate diol can be a random copolymer or a block copolymer.
[0014] In the present invention, specific examples of C1-C5 alkyl groups include, but are not limited to, methyl, ethyl, n-propyl, isopropyl, n-butyl, sec-butyl, isobutyl, tert-butyl, n-pentyl, isopentyl, tert-pentyl or neopentyl.
[0015] The number average molecular weight of the modified carbon dioxide based polycarbonate diol is preferably 1500-4000, such as 1500, 1800, 2000, 2200, 2500, 2800, 3000, 3200, 3500, 3800, 4000 or any value therebetween.
[0016] In a preferred embodiment, the volume ratio of component A to component B is (1-2):1, such as 1:1, 1.1:1, 1.2:1, 1.3:1, 1.4:1, 1.5:1, 1.6:1, 1.7:1, 1.8:1, 1.9:1, 2:1 or any value therebetween.
[0017] In a preferred embodiment, in component A, the content of the isocyanate di-terminated polyurethane prepolymer is 20-60 parts by weight, such as 20, 25, 30, 35, 40, 45, 50, 55, 60 parts by weight or any value therebetween; the content of the first thermally conductive filler is 45-85 parts by weight, such as 45, 50, 55, 60, 65, 70, 75, 80, 85 parts by weight or any value therebetween; the content of the first auxiliary agent is 0.1-5 parts by weight, such as 0.1, 0.5, 1, 2, 3, 4, 5 parts by weight or any value therebetween.
[0018] In a preferred embodiment, in component B, the content of the polyether polyol is 10-30 parts by weight, such as 10, 12, 15, 18, 20, 22, 25, 28, 30 parts by weight or any value therebetween; the content of the polybutadiene polyol is 10-20 parts by weight, such as 10, 12, 15, 18, 20 parts by weight or any value therebetween; the content of the small molecule polyol is 1-5 parts by weight, such as 1, 2, 3, 4, 5 parts by weight or any value therebetween. any value therebetween; the content of the second thermally conductive filler is 50-80 parts by weight, such as 50, 55, 60, 65, 70, 75, 80 parts by weight or any value therebetween; the content of the second catalyst is 0-1 part by weight, such as 0, 0.2, 0.4, 0.6, 0.8, 1 part by weight or any value therebetween; the content of the second auxiliary agent is 0.1-5 parts by weight, such as 0.1, 0.5, 1, 2, 3, 4, 5 parts by weight or any value therebetween.
[0019] The modified carbon dioxide-based polycarbonate diol can be obtained commercially or prepared according to various existing methods. In a preferred embodiment, the modified carbon dioxide-based polycarbonate diol is prepared according to the following method:
[0020] S1. placing the third catalyst in a high-pressure reactor, evacuating the high-pressure reactor at 50-80°C for at least 2 hours and filling it with CO2, adding propylene oxide and 1,2-epoxy-4-vinylcyclohexane into the high-pressure reactor under the protection of CO2, stirring, introducing CO2 into the reactor through a CO2 pressure regulator, placing the high-pressure reactor in a constant temperature bath at 28.5-32.0atm for copolymerization reaction for 4-8 hours, cooling the high-pressure reactor to below 20°C after the reaction, and slowly releasing the remaining CO2 to obtain a carbon dioxide-based polycarbonate diol;
[0021] S2, adding carbon dioxide-based polycarbonate diol, 3-mercaptopropyltrialkoxysilane, a free radical photoinitiator and an organic solvent into a reaction kettle and stirring until the solid is completely dissolved, and then reacting under ultraviolet light to obtain a mercapto-ene reaction product;
[0022] S3, concentrating the mercapto-ene reaction product, then slowly adding it into a non-solvent to precipitate a polymer, filtering and drying to obtain a modified carbon dioxide-based polycarbonate diol.
[0023] In a preferred embodiment, the molar ratio of the third catalyst to the total amount of propylene oxide and 1,2-epoxy-4-vinylcyclohexane is 1:(2000-7000), such as 1:2000, 1:2500, 1:3000, 1:3500, 1:4000, 1:4500, 1:5000, 1:5500, 1:6000, 1:6500, 1:7000 or any value therebetween.
[0024] In a preferred embodiment, the molar ratio of 1,2-epoxy-4-vinylcyclohexane to propylene oxide is 1:(13-55), such as 1:13, 1:15, 1:20, 1:25, 1:30, 1:35, 1:40, 1:45, 1:50, 1:55 or any value therebetween.
[0025] In a preferred embodiment, the third catalyst is selected from one or more of a carboxylate zinc catalytic system, a phenol oxide zinc catalytic system, a β-diimine zinc catalytic system, a pyridine-zinc catalytic system, a porphyrin catalytic system, a SalenMX catalytic system, a rare earth catalytic system, a double metal cyanide catalytic system and a supported catalytic system.
[0026] The free radical photoinitiator can be any existing compound that can absorb ultraviolet light energy to generate free radicals, thereby initiating a thiol-ene click reaction between a thiol group and an olefin group. In a preferred embodiment, the free radical photoinitiator is selected from 2-hydroxy-2-methyl-1-phenyl-1-propanone, 1-hydroxycyclohexyl phenyl ketone, 2-hydroxy-4-(2-hydroxyethoxy)-2-methylphenyl propiophenone, 2,4,6-trimethylbenzoyl-diphenylphosphine oxide, 2,4,6-trimethylbenzoylphenylphosphonic acid ethyl ester, bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide, 2-methyl-1-[4-(methylthio)phenyl]-2-(4-morpholinyl)-1-propanone, 2-phenylbenzyl-2-dimethylamine-1-(4-morpholinylbenzylphenyl)butanone, 4-benzoyl-4'-methyl-diphenyl sulfide, 2-(4-methylbenzyl)-2-( One or more of dimethylamino)-1-(4-morpholinophenyl)-1-butanone, 1,1'-(methylenebis-4,1-phenylene)bis[2-hydroxy-2-methyl-1-propanone], 2,2-dimethoxy-2-phenylacetophenone, 2,2-diethoxy-1-hexanophenone, bis-2,6-difluoro-3-pyrrolophenyl titanocene, methyl benzoylformate, benzophenone, 4-methylbenzophenone, 4-phenylbenzophenone, 4-chlorobenzophenone, methyl o-benzoylbenzoate, ethyl 4-dimethylaminobenzoate, isooctyl p-dimethylaminobenzoate, 4,4'-bis(diethylamino)benzophenone, isopropylthioxanthone, 2,4-diethylthioxanthone and 2-ethylanthraquinone.
[0027] In a preferred embodiment, in the preparation process of isocyanate di-terminated polyurethane prepolymer, the amount of the modified carbon dioxide-based polycarbonate diol is 10-30 parts by weight, such as 10, 12, 18, 20, 22, 25, 28, 30 parts by weight or any value therebetween; the amount of the castor oil polyol is 5-10 parts by weight, such as 5, 6, 7, 8, 9, 10 parts by weight or any value therebetween; the amount of the polyisocyanate is 5-15 parts by weight, such as 5, 8, 10, 12, 15 parts by weight or any value therebetween; the amount of the first catalyst is 0-1 part by weight, such as 0, 0.2, 0.4, 0.6, 0.8, 1 part by weight or any value therebetween.
[0028] The polyisocyanate is a compound with two or more isocyanate groups at the terminal of the molecular chain, and can be specifically an aromatic isocyanate and / or an aliphatic isocyanate, and specific examples thereof include but are not limited to: one or more of toluene-2,4-diisocyanate, 4,4'-diphenylmethane diisocyanate, hexamethylene diisocyanate, cyclohexyl diisocyanate, isophorone diisocyanate, lysine diisocyanate, liquefied diphenylmethane diisocyanate, low-viscosity HDI trimer and polymethylene polyphenyl polyisocyanate.
[0029] In a preferred embodiment, the polyether polyol is selected from one or more of polyethylene oxide glycol, polypropylene oxide glycol, polytetramethylene glycol and copolymerized glycols thereof.
[0030] In a preferred embodiment, the number average molecular weight of the polyether polyol is 400-1000, such as 400, 500, 600, 700, 800, 900, 1000 or any value therebetween.
[0031] In a preferred embodiment, the polybutadiene polyol is selected from one or more of hydroxyl-terminated polybutadiene polyol, hydrogenated hydroxyl-terminated polybutadiene polyol and hydroxyl-terminated polybutadiene-acrylonitrile polyol.
[0032] In a preferred embodiment, the number average molecular weight of the polybutadiene polyol is 1000-3000, such as 1000, 1200, 1500, 1800, 2000, 2200, 2500, 2800, 3000 or any value therebetween.
[0033] In a preferred embodiment, the small molecule polyol is selected from one or more of propylene glycol, butylene glycol, pentylene glycol, hexylene glycol, neopentyl glycol, cyclohexanedimethanol, glycerol, trimethylolpropane and triethanolamine.
[0034] In a preferred embodiment, the first catalyst and the second catalyst are each independently selected from one or more of dibutyltin dilaurate, 2,2-dimorpholinyl diethyl ether, an organic bismuth catalyst and stannous octoate.
[0035] In a preferred embodiment, the first thermally conductive filler and the second thermally conductive filler both contain thermally conductive filler I and thermally conductive filler II; the thermally conductive filler I has a particle size D 50 Spherical alumina with a particle size of 3-8 μm 50 The mixture is a mixture of spherical aluminum oxide with a particle size of 10-30 μm in a mass ratio of (0.5-2.0):1; the second thermally conductive filler is selected from one or more of magnesium oxide, zinc oxide, aluminum nitride, boron nitride, silicon carbide, graphene, carbon nanotubes, carbon fiber powder, aluminum hydroxide and magnesium hydroxide. 50 Spherical alumina with a particle size of 3-8 μm 50 The mass ratio of spherical alumina with a size of 10-30 μm is (0.5-2.0):1, and specifically can be 0.5:1, 0.8:1, 1:1, 1.2:1, 1.5:1, 1.8:1, 2:1 or any value therebetween.
[0036] In a preferred embodiment, the first auxiliary agent and the second auxiliary agent are each independently selected from one or more of an interface treatment agent, a defoamer, a thixotropic agent, a stabilizer, a water remover, a diluent, a toughening agent, an anti-aging agent, a pigment and a filler. Among them, specific examples of the interface treatment agent include, but are not limited to, one or more of γ-aminopropyltrimethoxysilane, γ-aminopropyltriethoxysilane, N-β-(aminoethyl)-γ-aminopropyltrimethoxysilane, anilinemethyltriethoxysilane, γ-(2,3-epoxypropoxy)propyltrimethoxysilane, β-(3,4-epoxycyclohexyl)ethyltrimethoxysilane and γ-ureapropyltriethoxysilane. Specific examples of the defoamer include, but are not limited to, one or more of a polymer defoamer, a silicone defoamer and a mineral oil defoamer. In addition, the thixotropic agent, stabilizer, water remover, diluent, toughening agent, anti-aging agent, pigment and filler can all be conventionally selected in the art, which is known to those skilled in the art and will not be repeated here.
[0037] The preparation method of the carbon dioxide-based two-component polyurethane thermally conductive adhesive provided by the present invention comprises the following steps:
[0038] Preparation of component A: adding modified carbon dioxide-based polycarbonate diol and castor oil polyol into a reaction kettle, heating to 110-130° C., stirring and mixing evenly under a vacuum degree of less than -0.085 MPa, and performing a dehydration treatment for 1-2 hours, then cooling to room temperature, introducing dry nitrogen to restore normal pressure, adding polyisocyanate and a first catalyst, stirring while heating, heating to 70-80° C., and continuing to react for 3-5 hours under nitrogen protection, then adding a first thermal conductive filler and an optional first auxiliary agent, stirring and mixing evenly while evacuating, to obtain component A;
[0039] Preparation of component B: polyether polyol, polybutadiene polyol, small molecule polyol, second thermal conductive filler and optional second catalyst and second auxiliary agent are stirred and mixed evenly, then heated to 110-130° C., dehydrated under vacuum degree lower than -0.085 MPa, cooled to room temperature, and then introduced with dry nitrogen to restore normal pressure to obtain component B.
[0040] The key of the present invention is to introduce a modified carbon dioxide-based polycarbonate diol having a structural unit derived from propylene oxide and having a six-membered ring, a flexible sulfur-containing group and a trialkoxysilane structural unit on the basis of a traditional polyurethane adhesive. This special structure can not only significantly improve the bonding strength of the polyurethane adhesive, but also can bridge with the thermal conductive filler through a coupling reaction, so that the thermal conductive filler can be better dispersed, and the anti-sedimentation performance of the thermal conductive adhesive is improved. The thermal conductivity of the polyurethane adhesive obtained is very excellent. In addition, the modified carbon dioxide-based polycarbonate diol uses carbon dioxide as a raw material, and the corresponding polyurethane adhesive has the advantages of being environmentally friendly, green and environmentally friendly, and low cost, which helps to achieve carbon emission reduction, conforms to the concept of sustainable development, and conforms to economic and social benefits. DETAILED DESCRIPTION
[0041] The present invention will be described in detail below through examples.
[0042] In the following preparation examples, propylene oxide is selected from P109309 of Shanghai Aladdin Biochemical Technology Co., Ltd.; 1,2-epoxy-4-vinylcyclohexane is selected from Celloxide 2000 of Daicel of Japan; and the photoinitiator DMPA is selected from 01049771 of Shanghai Titan Technology Co., Ltd.
[0043] In the following examples and comparative examples, castor oil polyol is selected from Japan Ito Oil Co., Ltd., with the brand name URIC AC008; polyether polyol is purchased from Kukto Chemical Co., Ltd., with the brand name GY420; polybutadiene polyol is purchased from Japan Soda Co., Ltd., with the brand name G-2000; small molecule polyol is 1,4-butanediol, purchased from A040124 of Anage Chemical; polyisocyanate is polymethylene polyphenyl polyisocyanate, selected from PM-2025 of Wanhua Chemical Co., Ltd.; the first catalyst and the second catalyst are both 2,2-dimorpholinyl diethyl ether, selected from B802012 of Shanghai MacLean Biochemical Technology Co., Ltd.; the interface treatment agent is γ-aminopropyl trimethoxysilane, selected from KBM-903 of Shin-Etsu Co., Ltd. of Japan; the defoamer is purchased from BYK, with the brand name BYK535; the thixotropic agent is fumed silica purchased from Cabot Corporation, with the brand name TS720; the first thermal conductive filler is spherical alumina, D 50 The particle sizes are 5μm and 20μm respectively; the second thermal conductive filler is spherical aluminum nitride, D 50 The particle size is 35μm.
[0044] In the following examples and comparative examples, the amount of each raw material used is measured in parts by weight.
[0045] Preparation Example 1
[0046] This preparation example is used to illustrate the preparation of modified carbon dioxide-based polycarbonate diol. The specific reaction steps are as follows:
[0047] Step 1: 0.68 g of SalenCo (III) NO3 catalyst is placed in a high-pressure reactor, the reactor is vacuumed and filled with CO2 at 60°C for 2 hours, 209 g of propylene oxide and 29.8 g of 1,2-epoxy-4-vinylcyclohexane are added to the reactor under the protection of CO2, and stirred, CO2 is introduced into the reactor through a CO2 pressure regulator, and the autoclave is placed in a constant temperature bath at 28.5-32.0 atm for copolymerization reaction for 6 hours. After the reaction is completed, the reactor is cooled to below 20°C and the remaining CO2 is slowly released to obtain 397 g of carbon dioxide-based polycarbonate diol;
[0048] Step 2: Add 350 g of carbon dioxide-based polycarbonate diol, 28.52 g of 3-mercaptopropyltrimethoxysilane, 2.68 g of free radical photoinitiator DMPA and 500 mL of thoroughly dried tetrahydrofuran into a reaction kettle, then stir the mixture until the solid is completely dissolved, and irradiate the mixture under ultraviolet light for 8 hours to obtain a mercapto-ene reaction product;
[0049] Step 3: Concentrate the mercapto-ene reaction product, then slowly add it into non-solvent anhydrous ether to dissolve and precipitate the polymer, and obtain a modified carbon dioxide-based polycarbonate diol with a number average molecular weight of 3470 after filtering and drying.
[0050] Preparation Example 2
[0051] This preparation example is used to illustrate the preparation of modified carbon dioxide-based polycarbonate diol. The specific reaction steps are as follows:
[0052] Step 1: 0.11 g of SalenCo (III) NO3 catalyst is placed in a high-pressure reactor, the reactor is vacuumed and filled with CO2 at 60°C for 2 hours, 209 g of propylene oxide and 29.8 g of 1,2-epoxy-4-vinylcyclohexane are added to the reactor under the protection of CO2, and stirred, CO2 is introduced into the reactor through a CO2 pressure regulator, and the autoclave is placed in a constant temperature bath at 28.5-32.0 atm for copolymerization reaction, the reaction time is 6 hours, and after the reaction is completed, the reactor is cooled to below 20°C and the remaining CO2 is slowly released to obtain 244 g of carbon dioxide-based polycarbonate diol;
[0053] Step 2: Add 200 g of carbon dioxide-based polycarbonate diol, 33.16 g of 3-mercaptopropyltrimethoxysilane, 3.10 g of free radical photoinitiator DMPA and 300 mL of thoroughly dried tetrahydrofuran into a reaction kettle, then stir the mixture until the solid is completely dissolved, and irradiate the reaction under ultraviolet light for 8 hours;
[0054] Step 3: Concentrate the mercapto-ene reaction product, then slowly add it into non-solvent anhydrous ether to dissolve and precipitate the polymer, and obtain a modified carbon dioxide-based polycarbonate diol with a number average molecular weight of 1780 after filtering and drying.
[0055] Preparation Example 3
[0056] 10.0 mg of DMC catalyst and 25.0 g of sebacic acid chain transfer agent were placed in a high-pressure reactor. The reactor was evacuated and filled with CO2 at 60°C for 2 h. Under the protection of CO2, 100 g of propylene oxide was added into the reactor and stirred. CO2 was introduced into the reactor through a CO2 pressure regulator. The autoclave was placed in a constant temperature bath at 28.5-32.0 atm for copolymerization. The reaction time was 6 h. After the reaction, the reactor was cooled to below 20°C to slowly release the remaining CO2. 90 mg of tri(pentafluorophenyl)borane and 10 g of propylene oxide were added into the reactor. The temperature was raised to 100°C and the reaction was continued for 2 h. After the reaction, the reactor used for the polymerization reaction was cooled to room temperature with a cold water bath at a temperature of 12-15°C, the unreacted propylene oxide was evaporated, and the residue was dried in a vacuum drying oven at 40°C to constant weight, thereby obtaining 126.9 g of poly(carbonate-ether) diol with a number average molecular weight of 1500.
[0057] Example 1 Preparation of carbon dioxide-based two-component polyurethane thermally conductive adhesive
[0058] Preparation of component A: 20 parts of the modified carbon dioxide-based polycarbonate diol prepared in Preparation Example 1 and 7.5 parts of castor oil polyol were put into a reaction kettle, heated to 120°C, stirred and mixed evenly under a vacuum degree of less than -0.085 MPa, and dehydrated for 2 hours, then cooled and introduced into dry nitrogen to restore normal pressure, 10 parts of polyisocyanate and 0.6 parts of the first catalyst were added, heated and stirred, and the temperature was raised to 75°C and the reaction was continued for 4 hours under nitrogen protection, followed by the addition of 10 parts of D 50 35μm spherical aluminum nitride, 35 parts D 50 20 μm spherical alumina, 20 parts D 50 5 μm spherical alumina, 1 part of γ-aminopropyltrimethoxysilane, 0.2 parts of defoamer BYK535 and 2 parts of fumed silica TS720 were added, stirred and mixed for 1 hour under nitrogen protection, and then vacuum degassed for 1 hour to obtain component A;
[0059] Preparation of component B: 20 parts of polyether polyol, 15 parts of polybutadiene polyol and 2 parts of small molecule polyol were put into another reactor, and then 0.6 parts of the second catalyst and 10 parts of D 50 35μm spherical aluminum nitride, 35 parts D 50 20 μm spherical alumina and 20 parts of D 505 μm spherical alumina, 1 part of γ-aminopropyltrimethoxysilane, 0.2 parts of defoamer BYK535 and 2 parts of fumed silica TS720 are stirred and mixed, then heated to 120°C, dehydrated for 2 hours under a vacuum degree of less than -0.085 MPa, cooled and introduced with dry nitrogen to restore to normal pressure, thus obtaining component B;
[0060] The volume ratio of component A to component B in the carbon dioxide-based two-component polyurethane thermal conductive adhesive is 2:1, wherein component A and component B are stored independently of each other.
[0061] Example 2 Preparation of carbon dioxide-based two-component polyurethane thermally conductive adhesive
[0062] Preparation of component A: 10 parts of the modified carbon dioxide-based polycarbonate diol prepared in Preparation Example 1 and 5 parts of castor oil polyol were put into a reaction kettle, heated to 120°C, stirred and mixed evenly under a vacuum degree of less than -0.085 MPa, and dehydrated for 2 hours, then cooled and introduced into dry nitrogen to restore normal pressure, 5 parts of polyisocyanate and 0.3 parts of the first catalyst were added, heated and stirred, and the temperature was raised to 75°C and the reaction was continued for 4 hours under nitrogen protection, and then 5 parts of D were added. 50 35μm spherical aluminum nitride, 25 parts D 50 20 μm spherical alumina, 15 parts D 50 5 μm spherical alumina, 0.7 parts of γ-aminopropyltrimethoxysilane, 0.1 parts of defoamer BYK535 and 2 parts of fumed silica TS720 were added, stirred and mixed for 1 hour under nitrogen protection, and then vacuum degassed for 1 hour to obtain component A;
[0063] Preparation of component B: 10 parts of polyether polyol, 10 parts of polybutadiene polyol and 1.5 parts of small molecule polyol were put into another reactor, and then 0.3 parts of the second catalyst were added, and 5 parts of D were added in sequence. 50 35μm spherical aluminum nitride, 25 parts D 50 20 μm spherical alumina, 15 parts D 50 5 μm spherical alumina, 0.7 parts of γ-aminopropyltrimethoxysilane, 0.1 parts of defoamer BYK535 and 2 parts of fumed silica TS720 are stirred and mixed, then heated to 120°C, dehydrated for 2 hours under a vacuum degree of less than -0.085 MPa, cooled and introduced with dry nitrogen to restore to normal pressure, thus obtaining component B;
[0064] The volume ratio of component A to component B in the carbon dioxide-based two-component polyurethane thermal conductive adhesive is 1:1, wherein component A and component B are stored independently of each other.
[0065] Example 3 Preparation of carbon dioxide-based two-component polyurethane thermally conductive adhesive
[0066] Preparation of component A: 30 parts of the modified carbon dioxide-based polycarbonate diol prepared in Preparation Example 1 and 10 parts of castor oil polyol were added to a reaction kettle, heated to 120°C, stirred and mixed evenly under a vacuum degree of less than -0.085 MPa, and dehydrated for 2 hours, then cooled and introduced into dry nitrogen to restore normal pressure, 15 parts of polyisocyanate and 1 part of the first catalyst were added, heated and stirred, and the temperature was raised to 75°C and the reaction was continued for 4 hours under nitrogen protection, followed by the addition of 15 parts of D 50 35μm spherical aluminum nitride, 42 parts D 50 20 μm spherical alumina, 28 parts D 50 5 μm spherical alumina, 1.4 parts of γ-aminopropyltrimethoxysilane, 0.3 parts of defoamer BYK535 and 2 parts of fumed silica TS720 were added, stirred and mixed for 1 hour under nitrogen protection, and then vacuum degassed for 1 hour to obtain component A;
[0067] Preparation of component B: 30 parts of polyether polyol, 20 parts of polybutadiene polyol and 3 parts of small molecule polyol were put into another reactor, and then 1 part of the second catalyst was added, and 15 parts of D 50 35μm spherical aluminum nitride, 42 parts D 50 20 μm spherical alumina, 28 parts D 50 5 μm spherical alumina, 1.4 parts of γ-aminopropyltrimethoxysilane, 0.3 parts of defoamer BYK535 and 2 parts of fumed silica TS720 are stirred and mixed, then heated to 120°C, dehydrated for 2 hours under a vacuum degree of less than -0.085 MPa, cooled and introduced with dry nitrogen to restore to normal pressure, thus obtaining component B;
[0068] The volume ratio of component A to component B in the carbon dioxide-based two-component polyurethane thermal conductive adhesive is 1.5:1, wherein component A and component B are stored independently of each other.
[0069] Example 4
[0070] A carbon dioxide-based two-component polyurethane thermally conductive adhesive was prepared according to the method of Example 1, except that the modified carbon dioxide-based polycarbonate diol prepared in Preparation Example 1 was replaced by the modified carbon dioxide-based polycarbonate diol prepared in Preparation Example 2 in equal parts by weight, and the remaining conditions were the same as in Example 1 to obtain a carbon dioxide-based two-component polyurethane thermally conductive adhesive.
[0071] Example 5
[0072] A carbon dioxide-based two-component polyurethane thermally conductive adhesive was prepared according to the method of Example 2, except that the modified carbon dioxide-based polycarbonate diol prepared in Preparation Example 1 was replaced by the modified carbon dioxide-based polycarbonate diol prepared in Preparation Example 2 in equal parts by weight, and the remaining conditions were the same as in Example 2 to obtain a carbon dioxide-based two-component polyurethane thermally conductive adhesive.
[0073] Example 6
[0074] A carbon dioxide-based two-component polyurethane thermally conductive adhesive was prepared according to the method of Example 3, except that the modified carbon dioxide-based polycarbonate diol prepared in Preparation Example 1 was replaced by the modified carbon dioxide-based polycarbonate diol prepared in Preparation Example 2 in equal parts by weight, and the remaining conditions were the same as in Example 3 to obtain a carbon dioxide-based two-component polyurethane thermally conductive adhesive.
[0075] Comparative Example 1
[0076] A carbon dioxide-based two-component polyurethane thermally conductive adhesive was prepared according to the method of Example 1, except that the modified carbon dioxide-based polycarbonate diol prepared in Preparation Example 1 was replaced by the same weight portion of the poly(carbonate-ether) diol prepared in Preparation Example 3, and the remaining conditions were the same as in Example 1 to obtain a carbon dioxide-based two-component polyurethane thermally conductive adhesive.
[0077] Comparative Example 2
[0078] A carbon dioxide-based two-component polyurethane thermally conductive adhesive was prepared according to the method of Example 2, except that the modified carbon dioxide-based polycarbonate diol prepared in Preparation Example 1 was replaced by the same weight portion of poly(carbonate-ether) diol prepared in Preparation Example 3, and the remaining conditions were the same as in Example 2 to obtain a carbon dioxide-based two-component polyurethane thermally conductive adhesive.
[0079] Comparative Example 3
[0080] A carbon dioxide-based two-component polyurethane thermally conductive adhesive was prepared according to the method of Example 3, except that the modified carbon dioxide-based polycarbonate diol prepared in Preparation Example 1 was replaced by the same weight portion of poly(carbonate-ether) diol prepared in Preparation Example 3, and the remaining conditions were the same as in Example 3 to obtain a carbon dioxide-based two-component polyurethane thermally conductive adhesive.
[0081] Comparative Example 4
[0082] A two-component polyurethane thermally conductive adhesive was prepared according to the method of Example 1, except that the modified carbon dioxide-based polycarbonate diol prepared in Preparation Example 1 was replaced by an equal weight portion of commercial polyester diol (Dynacoll 7250 from Evonik). The remaining conditions were the same as in Example 1 to obtain a two-component polyurethane thermally conductive adhesive.
[0083] Test Case
[0084] The samples obtained from Examples 1-6 and Comparative Examples 1-4 were subjected to the following performance tests:
[0085] (1) Adhesive properties (tensile shear strength): Tested according to standard GB / T 7124-2008 "Determination of tensile shear strength of adhesives (rigid material to rigid material)". Specifically, an aluminum plate with a size of 100 mm × 25 mm × 2 mm was selected, two aluminum plates were overlapped together, the bonding area was 12.5 mm × 25 mm, and the thickness of the adhesive layer was ensured to be 0.2 mm. The overlapped specimens were placed in a constant temperature and humidity room with a temperature of 25°C and a humidity of 50% RH for seven days at room temperature. The tensile shear strength was tested using a universal material tensile force testing machine at a tensile speed of 5 mm / min. The results are shown in Table 1.
[0086] (2) Thermal conductivity: First, the two-component polyurethane thermal conductive adhesive was injected into a standard tetrafluoroethylene mold after passing through a static mixer, scraped flat, and placed in a constant temperature and humidity room at a temperature of 25°C and a humidity of 50% RH for room temperature curing for 7 days; then the cured sample was taken out and tested using the method in ISO 22007-2, and the thermal conductivity data was recorded. The results are shown in Table 1.
[0087] Table 1
[0088]
[0089] From the results in Table 1, it can be seen that the carbon dioxide-based two-component polyurethane thermal conductive adhesive provided by the present invention still has a high bonding strength when the thermal conductivity coefficient is obtained above 1.86W / (m·K), that is, it has both good bonding strength and thermal conductivity. In addition, the modified carbon dioxide-based polycarbonate diol uses carbon dioxide as a raw material, and the corresponding two-component polyurethane thermal conductive adhesive has the advantages of being environmentally friendly, green and environmentally friendly, and low cost, which helps to achieve carbon emission reduction, conforms to the concept of sustainable development, and meets economic and social benefits.
[0090] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations on the present invention. A person skilled in the art may change, modify, replace and modify the above embodiments within the scope of the present invention without departing from the principles and intent of the present invention.
Claims
1. A carbon dioxide-based two-component polyurethane thermally conductive adhesive, characterized in that: The invention comprises component A and component B in a volume ratio of (1-2):1; the component A comprises an isocyanate diblocked polyurethane prepolymer, a first thermally conductive filler and an optional first auxiliary agent, wherein the isocyanate diblocked polyurethane prepolymer is obtained by subjecting a modified carbon dioxide-based polycarbonate diol, a castor oil polyol and a polyisocyanate to a nucleophilic addition reaction in the presence of a first catalyst; the component B comprises a polyether polyol, a polybutadiene polyol, a small molecule polyol, a second thermally conductive filler and an optional second catalyst and a second auxiliary agent; the modified carbon dioxide-based polycarbonate diol simultaneously comprises a structural unit represented by formula (I), a structural unit represented by formula (II) and a structural unit represented by formula (III): In formula (III), R1, R2 and R3 are each independently a C1-C5 alkyl group; In component A, the content of the isocyanate di-terminated polyurethane prepolymer is 20-60 parts by weight, the content of the first thermally conductive filler is 45-85 parts by weight, and the content of the first auxiliary agent is 0.1-5 parts by weight; in component B, the content of the polyether polyol is 10-30 parts by weight, the content of the polybutadiene polyol is 10-20 parts by weight, the content of the small molecule polyol is 1-5 parts by weight, the content of the second thermally conductive filler is 50-80 parts by weight, the content of the second catalyst is 0-1 parts by weight, and the content of the second auxiliary agent is 0.1-5 parts by weight; In the preparation process of isocyanate di-terminated polyurethane prepolymer, the amount of the modified carbon dioxide-based polycarbonate diol is 10-30 parts by weight, the amount of the castor oil polyol is 5-10 parts by weight, the amount of the polyisocyanate is 5-15 parts by weight, and the amount of the first catalyst is 0-1 part by weight.
2. The carbon dioxide-based two-component polyurethane thermally conductive adhesive according to claim 1, characterized in that: The modified carbon dioxide-based polycarbonate diol is prepared according to the following method: S1. placing the third catalyst in a high-pressure reactor, evacuating the high-pressure reactor at 50-80°C for at least 2 hours and filling it with CO2, adding propylene oxide and 1,2-epoxy-4-vinylcyclohexane into the high-pressure reactor under the protection of CO2, stirring, introducing CO2 into the reactor through a CO2 pressure regulator, placing the high-pressure reactor in a constant temperature bath at 28.5-32.0atm for copolymerization reaction for 4-8 hours, cooling the high-pressure reactor to below 20°C after the reaction, and slowly releasing the remaining CO2 to obtain a carbon dioxide-based polycarbonate diol; S2, adding carbon dioxide-based polycarbonate diol, 3-mercaptopropyltrialkoxysilane, a free radical photoinitiator and an organic solvent into a reaction kettle and stirring until the solid is completely dissolved, and then reacting under ultraviolet light to obtain a mercapto-ene reaction product; S3, concentrating the mercapto-ene reaction product, then slowly adding it into a non-solvent to precipitate the polymer, filtering and drying to obtain a modified carbon dioxide-based polycarbonate diol.
3. The carbon dioxide-based two-component polyurethane thermally conductive adhesive according to claim 2, characterized in that: The molar ratio of the third catalyst to the total amount of propylene oxide and 1,2-epoxy-4-vinylcyclohexane is 1:(2000-7000); the molar ratio of 1,2-epoxy-4-vinylcyclohexane to propylene oxide is 1:(13-55).
4. The carbon dioxide-based two-component polyurethane thermally conductive adhesive according to claim 2, characterized in that: The third catalyst is selected from at least one of a carboxylate zinc catalytic system, a phenol oxide zinc catalytic system, a β-diimine zinc catalytic system, a pyridine-zinc catalytic system, a porphyrin catalytic system, a SalenMX catalytic system, a rare earth catalytic system, a double metal cyanide catalytic system and a supported catalytic system.
5. The carbon dioxide-based two-component polyurethane thermally conductive adhesive according to claim 2, characterized in that: The free radical photoinitiator is selected from 2-hydroxy-2-methyl-1-phenyl-1-propanone, 1-hydroxycyclohexyl phenyl ketone, 2-hydroxy-4-(2-hydroxyethoxy)-2-methylphenyl propiophenone, 2,4,6-trimethylbenzoyl-diphenylphosphine oxide, 2,4,6-trimethylbenzoylphenylphosphonic acid ethyl ester, bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide, 2-methyl-1-[4-(methylthio)phenyl]-2-(4-morpholinyl)-1-propanone, 2-phenylbenzyl-2-dimethylamine-1-(4-morpholinylbenzylphenyl)butanone, 4-benzoyl-4'-methyl-diphenyl sulfide, 2-(4-methylbenzyl)-2-(dimethylamino)phenyl ...2-methyl-1-[4-(methylthio)phenyl]-2-(dimethylamino)phenyl phosphine oxide, 2-methyl-1-[4-(methylthio)phenyl]-2-(4-morpholinyl)-1-propanone, 2-phenylbenzyl-2-dimethylamine-1-(4-morpholinylbenzylphenyl)butanone, 2-methyl-1 )-1-(4-morpholinophenyl)-1-butanone, 1,1'-(methylenebis-4,1-phenylene)bis[2-hydroxy-2-methyl-1-propanone], 2,2-dimethoxy-2-phenylacetophenone, 2,2-diethoxy-1-hexanophenone, bis-2,6-difluoro-3-pyrrolophenyl titanocene, methyl benzoylformate, benzophenone, 4-methylbenzophenone, 4-phenylbenzophenone, 4-chlorobenzophenone, methyl o-benzoylbenzoate, ethyl 4-dimethylaminobenzoate, isooctyl p-dimethylaminobenzoate, 4,4'-bis(diethylamino)benzophenone, isopropylthioxanthone, 2,4-diethylthioxanthone and 2-ethylanthraquinone.
6. The carbon dioxide-based two-component polyurethane thermally conductive adhesive according to claim 1, characterized in that: The polyisocyanate is selected from one or more of toluene-2,4-diisocyanate, 4,4'-diphenylmethane diisocyanate, hexamethylene diisocyanate, cyclohexyl diisocyanate, isophorone diisocyanate, lysine diisocyanate, liquefied diphenylmethane diisocyanate, low-viscosity HDI trimer and polymethylene polyphenyl polyisocyanate.
7. The carbon dioxide-based two-component polyurethane thermally conductive adhesive according to claim 1, characterized in that: The polyether polyol is selected from one or more of polyethylene oxide glycol, polypropylene oxide glycol, polytetramethylene glycol and copolymerized glycols thereof; the number average molecular weight of the polyether polyol is 400-1000.
8. The carbon dioxide-based two-component polyurethane thermally conductive adhesive according to claim 1, characterized in that: The polybutadiene polyol is selected from one or more of terminal hydroxyl polybutadiene polyol, hydrogenated terminal hydroxyl polybutadiene polyol and terminal hydroxyl polybutadiene-acrylonitrile polyol; the number average molecular weight of the polybutadiene polyol is 1000-3000.
9. The carbon dioxide-based two-component polyurethane thermally conductive adhesive according to claim 1, characterized in that: The small molecule polyol is selected from one or more of propylene glycol, butylene glycol, pentylene glycol, hexylene glycol, neopentyl glycol, cyclohexanedimethanol, glycerol, trimethylolpropane and triethanolamine.
10. The carbon dioxide-based two-component polyurethane thermally conductive adhesive according to claim 1, characterized in that: The first catalyst and the second catalyst are each independently selected from one or more of dibutyltin dilaurate, 2,2-dimorpholinyl diethyl ether, an organic bismuth catalyst and stannous octoate.
11. The carbon dioxide-based two-component polyurethane thermally conductive adhesive according to claim 1, characterized in that: The first thermally conductive filler and the second thermally conductive filler both contain thermally conductive filler I and thermally conductive filler II; the thermally conductive filler I has a particle size D 50 Spherical alumina with a particle size of 3-8 μm 50 It is a mixture of spherical aluminum oxide with a size of 10-30 μm in a mass ratio of (0.5-2.0):1; the second thermally conductive filler is selected from one or more of magnesium oxide, zinc oxide, aluminum nitride, boron nitride, silicon carbide, graphene, carbon nanotubes, carbon fiber powder, aluminum hydroxide and magnesium hydroxide.
12. The carbon dioxide-based two-component polyurethane thermally conductive adhesive according to claim 1, characterized in that: The first auxiliary agent and the second auxiliary agent are each independently selected from one or more of an interface treatment agent, a defoaming agent, a thixotropic agent, a stabilizer, a water scavenger, a diluent, a toughening agent, an anti-aging agent, a pigment and a filler.
13. The method for preparing the carbon dioxide-based two-component polyurethane thermally conductive adhesive according to any one of claims 1 to 12, characterized in that: The method comprises the following steps: Preparation of component A: adding modified carbon dioxide-based polycarbonate diol and castor oil polyol into a reaction kettle, heating to 110-130° C., stirring and mixing evenly under a vacuum degree of less than -0.085 MPa, and performing a dehydration treatment for 1-2 hours, then cooling to room temperature, introducing dry nitrogen to restore normal pressure, adding polyisocyanate and a first catalyst, stirring while heating, heating to 70-80° C., and continuing to react for 3-5 hours under nitrogen protection, then adding a first thermal conductive filler and an optional first auxiliary agent, stirring and mixing evenly while evacuating, to obtain component A; Preparation of component B: polyether polyol, polybutadiene polyol, small molecule polyol, second thermal conductive filler and optional second catalyst and second auxiliary agent are stirred and mixed evenly, then heated to 110-130° C., dehydrated under vacuum degree lower than -0.085 MPa, cooled to room temperature, and then introduced with dry nitrogen to restore normal pressure to obtain component B.
Citation Information
Patent Citations
Anti-flaming water-borne polyurethane and preparation method thereof, and adhesive and preparation method thereof
CN106750175A
Carbon dioxide based waterborne polyurethane dispersoid, preparation method and carbon dioxide based waterborne polyurethane pressure-sensitive adhesive
CN108314770A